STUDI ORGANOLEPTIK IKAN SELAR (Selaroides leptolepis) UNTUK MENENTUKAN KELAYAKAN KONSUMSI BERDASARKAN LAMA PENYIMPANAN - Putalan, Reinal; Ariany, septian palma; Azzahra Sudirman, Azisah; Nusi, Fakhrunnisa; Mi'raz, Nurhawalia (Program Vokasi UNG, 2025)
This study aims to evaluate the consumption feasibility of Selar fish (Selaroides leptolepis) during storage at ambient temperature over a 24-hour period through organoleptic observation. The assessed parameters included the condition of the eyes, gills, mucus, flesh, texture, and aroma, observed every two hours using a scoring sheet based on SNI 2729:2013. The evaluation results revealed that organoleptic quality degradation became significant after the 4th hour, as the average scores fell below the acceptable threshold (≥7). Statistical analysis yielded a confidence interval for fresh fish of 7.66 < μ < 8.13, whereas fish experiencing quality deterioration showed a confidence interval of 3.67 < μ < 4.24. These findings indicate that without active temperature control, Selar fish should be consumed within a maximum of four hours post-harvest. This study provides a scientific basis for implementing effective post-harvest handling practices to preserve fish quality and ensure food safety at the local level.